1982
DOI: 10.1002/macp.1982.021831018
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic implications of the end group structure in radical telechelic polybutadienes as studied by NMR

Abstract: 270 MHz 'H NMR spectra were used to study the structure of end groups and terminal monomeric units in polybutadienes produced by radical polymerization, initiated with hydrogen peroxide and a series of substituted benzoyl peroxides. The hydroxyl or aroyl groups were found to be bonded to the methylene end group of the 1,4-cis-, 1.4-frans-or 1,2-butadiene terminal units. The terminal units are richer in 1,2-structures than the backbone due to the influence of hydroxyl or of the aroyl groups on the relative reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…1 summarizes the chemical shifts of the hydroxymethyl end-groups observed by 1 H and 13 C NMR in the corresponding studies. As it can be seen, C OH and T OH groups are ambiguous since they led to different attributions: they have been regarded as equivalent by Fages and Pham 7,8) but slightly different by the other authors (Bresler et al 9,10) , Ramey et al 11) , and Vilar et al 12,13) ). Moreover, Fages and Pham 7,8) have suggested that the peak centred at 4.05 ppm corresponds to the G OH group coming from a transfer reaction.…”
Section: Oh Of Hydroxytelechelic Polybutadienesmentioning
confidence: 91%
“…1 summarizes the chemical shifts of the hydroxymethyl end-groups observed by 1 H and 13 C NMR in the corresponding studies. As it can be seen, C OH and T OH groups are ambiguous since they led to different attributions: they have been regarded as equivalent by Fages and Pham 7,8) but slightly different by the other authors (Bresler et al 9,10) , Ramey et al 11) , and Vilar et al 12,13) ). Moreover, Fages and Pham 7,8) have suggested that the peak centred at 4.05 ppm corresponds to the G OH group coming from a transfer reaction.…”
Section: Oh Of Hydroxytelechelic Polybutadienesmentioning
confidence: 91%
“…In the 1 H‐NMR spectrum [Fig. 1(b) ], the multiplet at 3.79 ppm can be assigned8, 9 to methine protons of the CH(CH 3 ) OH end groups.…”
Section: Resultsmentioning
confidence: 99%
“…In [204] it was demonstrated that during polymerization of butadiene with hydrogen peroxide in alcohol solution, alcohol end fragments (22% of total HG content) appeared in the polymer. I t was determined from the signals with chemical shifts at 3.67 ppm (methyl protons) and 1.805 ppm (methine protons) which correspond to the signals of the product with the end fragment -CH(OH)CH, specially prepared by anionic polymerization.…”
Section: C3hnhcoocand-c--mentioning
confidence: 99%